"Mistakes Can be Beautiful": Creative Engagement in Arts Integration for Early Adolescent Learners. (21st February 2019) - Anderson, Ross C.; Haney, Michele; Pitts, Christine; Porter, Lorna; Bousselot, Tracy
Abstract: In this study we explored students' perspectives and experiences engaging in an arts integration learning model during middle school through a pluralistic lens of creative engagement in learning. The sample included N  = 86 students in Grades 6–7 attending schools in fringe rural and urban locales from small and mid‐sized cities in the Pacific Northwest. We used a grounded theory approach to explore how creative engagement takes shape for the early adolescent learner. Our conceptual framework integrated intrapsychological (inward) processes with interpsychological (outward) exchange in the social environment of an arts integrated classroom. Schools involved in the study were part of a larger mixed‐methods research investigation and received intensive support for school‐wide arts integration development. We found that students valued opportunities in arts integration for (a) choice, (b) the expression of their unique interpretations, (c) taking risks and making mistakes, (d) recognizing and applying their Studio Habits of Mind, and (e) enhancement of motivation and engagement in learning. The need for competency, belonging, and autonomy were important conditions of the learning environment and the need for meaning‐making was paramount in the process of creative engagement.